Orthogonal Stability and Nonstability of a Generalized Quartic Functional Equation in Quasi-β-Normed Spaces. (15th February 2021) - Alessa, Nazek; Tamilvanan, K.; Loganathan, K.; Karthik, T. S.; Rassias, John Michael
Abstract : In this work, we examine the generalized Hyers-Ulam orthogonal stability of the quartic functional equation in quasi-β -normed spaces. Moreover, we prove that this functional equation is not stable in a special condition by a counterexample.